Pathogenicity and immune response against porcine circovirus type 3 infection in caesarean-derived, colostrum-deprived pigs. (18th January 2021) - Temeeyasen, Gun; Lierman, Shay; Arruda, Bailey L.; Main, Rodger; Vannucci, Fabio; Gimenez-Lirola, Luis G.; Piñeyro, Pablo E.
Abstract : Recently, a novel PCV species (PCV3) has been detected in cases associated with sow mortality, lesions consistent with porcine dermatitis and nephropathy syndrome, reproductive failure and multisystemic inflammation. The pathogenesis and clinical significance of PCV3 is still unclear. In this study, we investigated the immunopathogenesis of PCV3 in CD/CD pigs. Four treatment groups, PCV3 ( n =6), PCV3-KLH ( n =6), control ( n =3) and control-KLH ( n =3), were included with PCV3-positive tissue homogenate (gc=3.38×10 12 ml −1 and gc=1.04×10 11 ml −1 ), confirmed by quantitative PCR (qPCR) and next-generation sequencing. Clinical signs, viremia, viral shedding, systemic cytokines, humoral (IgG) and T-cellular response were evaluated for 42 days. At necropsy, tissues were collected for histological evaluation and PCV3 detection by qPCR and in situ hybridization. No significant clinical signs were observed through the study. Viremia was detected in both PCV3-inoculated groups from 3 days post-inoculation (p.i.) until the end of the study. Nasal shedding was detected from 3 to 28 days p.i. and faecal shedding was transient. PCV3 induced an early (7 days p.i.) and sustained (42 days p.i.) IgG response. No significant T-cell response was observed. Histological evaluation demonstrated lesions consistent with multisystemic inflammation and perivasculitis. All tissues evaluated were positive by qPCR and virus replication was confirmed by positive in situ hybridization. This study demonstrated the potential role of PCV3 in subclinical infection, producing a mild, multisystemic inflammatory response, prolonged viremia detectable for 42 days p.i., presence of IgG humoral response and viral shedding in nasal secretions. More research is required to understand and elucidate potential co-factors necessary in the manifestation and severity of clinical disease.